PENGARUH DISIPLIN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN BAGIAN TATA USAHAPADA RUMAH SAKIT UMUM DAERAH KAB KUANTAN SINGINGI - Emella Sari; Seno Andri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
This research was conducted on Rumah Sakit Umum Daerah Kab Kuansing, as for the purpose of this study was to determine the effect of work discipline and work motivation on employee performance in the administrasion department on Rumah Sakit Umum Daerah Kab Kuansing. Granting of discipline work and work motivation as indevendent variabels (X1,X2) While the employee performace as an independent variable (Y).This research is a causal associative research using quantitative methods research subjectEmployee administrasion department on Rumah Sakit Umum Daerah Kab Kuansing of the study was 42 employee,s. Data collection using questionnaires and subsequent interviews were processed and then tested through statistics through the SPSS program. Hypothesis testing uses a simple linear analysis method and multiple analysis with result showing that work discipline and work motivation have a positive and significant effect on employee performance at Rumah Sakit Umum Daerah Kab Kuansing. With the calculation of the coefficient of determination (R2) work discipline on employee performance the value of R square is 0,648 or 64,8% and work motivation on employee performance the value of R square is 0,246 or 24,6% and coefficient of determination (R2) store work discipline and work motivation on employee performance the value of R square is 0,693 or 6,93%. This show that the work discipline and work motivation gives an effect of 6,93% on employee performance at Rumah Sakit Umum Daerah Kab Kuansing, while remaining 30,7% is effected by other variables that aee not examined in this study. Keywords: work Discipline, work Motivation, Performance